2004
DOI: 10.5694/j.1326-5377.2004.tb06402.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting death in young offenders: a retrospective cohort study

Abstract: Objective: To examine predictors of death in young offenders who have received a custodial sentence using data routinely collected by juvenile justice services. Design: A retrospective cohort of 2849 (2625 male) 11–20‐year‐olds receiving their first custodial sentence between 1 January 1988 and 31 December 1999 was identified. Main outcome measures: Deaths, date and primary cause of death ascertained from study commencement to 1 March 2003 by data‐matching with the National Death Index; measures comprising yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 16 publications
(29 reference statements)
4
38
2
Order By: Relevance
“…Examples of the 23 original research articles that were rated as having a moderate consideration of multicultural health included: a study of young women and risk taking, which found young women from non-English-speaking backgrounds (NESB) were more likely to be involved in car accidents [57]; a study of snorkelling deaths, which found 10 out of 27 were 'NESB tourists' [58]; a study of homicides during psychotic episodes, which found that 19% (an over-representation) were from a 'NES background' [59]; a study predicting deaths among young offenders, which found that having a drug-related offence was a major predictor and that the risk of drug-related offences was 13 times greater for 'Asian' young offenders and two times greater for those from other non-English-speaking backgrounds [60]; a study of cosmetic surgery and health status noting that NESB women were less likely to undergo cosmetic surgery [61]; a study of the spread of Hepatitis C, finding that Vietnamese migrants and prisoners were more likely to share needles [62]; a study of the help-seeking behaviour of men with erectile dysfunction finding that NESB men with this problem were less likely to seek help [63]; a study of gestational diabetes noting a general prevalence of 3.6% 'north east Asian' and 'south east Asian' women having prevalence rates of 13.7% and 12.5% respectively [64]; a study of obesity and overweight in an obstetric population noting increasingly high body mass index (BMI) associated with 'minority ethnic descent' [65]; a study of Type 2 Diabetes in youth finding 'ethnic' young people were over-represented [66]; and an epidemiological study and discussion of child health in Australia, which noted the particular vulnerability of asylum seekers and the problems of institutional racism [67]. …”
Section: Resultsmentioning
confidence: 99%
“…Examples of the 23 original research articles that were rated as having a moderate consideration of multicultural health included: a study of young women and risk taking, which found young women from non-English-speaking backgrounds (NESB) were more likely to be involved in car accidents [57]; a study of snorkelling deaths, which found 10 out of 27 were 'NESB tourists' [58]; a study of homicides during psychotic episodes, which found that 19% (an over-representation) were from a 'NES background' [59]; a study predicting deaths among young offenders, which found that having a drug-related offence was a major predictor and that the risk of drug-related offences was 13 times greater for 'Asian' young offenders and two times greater for those from other non-English-speaking backgrounds [60]; a study of cosmetic surgery and health status noting that NESB women were less likely to undergo cosmetic surgery [61]; a study of the spread of Hepatitis C, finding that Vietnamese migrants and prisoners were more likely to share needles [62]; a study of the help-seeking behaviour of men with erectile dysfunction finding that NESB men with this problem were less likely to seek help [63]; a study of gestational diabetes noting a general prevalence of 3.6% 'north east Asian' and 'south east Asian' women having prevalence rates of 13.7% and 12.5% respectively [64]; a study of obesity and overweight in an obstetric population noting increasingly high body mass index (BMI) associated with 'minority ethnic descent' [65]; a study of Type 2 Diabetes in youth finding 'ethnic' young people were over-represented [66]; and an epidemiological study and discussion of child health in Australia, which noted the particular vulnerability of asylum seekers and the problems of institutional racism [67]. …”
Section: Resultsmentioning
confidence: 99%
“…In the USA, in Gluecks's cohort, rates of delinquency and mortality were found to be strongly interlinked (Laub and Vaillant, 2000). An Australian study associated mortality risk particularly with early or multiple detentions (Coffey et al, 2004). Data from the Netherlands showed links between convictions and mortality, particularly between active recidivism and unnatural deaths (Nieuwbeerta and Piquero, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Over the same period, in Victoria alone, 820 men and women who had been released from prison died unnatural deaths 4 . The study by Coffey and colleagues in this issue of the Journal (https://doi.org/10.5694/j.1326-5377.2004.tb06402.x) shows that the problem is not confined to adult offenders but affects juveniles as well 8 …”
mentioning
confidence: 99%
“…The high rate of unnatural deaths among offenders living in the community is a major public health issue, but what can we do to reduce these rates? One of the groups at greatest risk is injecting drug users — over half of the unnatural deaths examined in the earlier Victorian study were heroin related, 4 and drug‐related offences were an indicator of high mortality risk in the study by Coffey et al 8 Drug treatment and maintenance (methadone) programs lower the risk of death by overdose 9 . However, many of those at greatest risk are profoundly alienated from society, and we need to find ways to engage them.…”
mentioning
confidence: 99%